Limit theorems for the solutions of linear boundary-value problems for systems of differential equations - Pelekhata, O. B.; Reva, N. V. (Ukrains’kyi Matematychnyi Zhurnal, 2019)
UDC 517.927 We establish sufficient conditions for the sequence of solutions of general boundary-value problems for systems of linear ordinary differential equations of any order on a finite interval to be convergent in the uniform norm.